An Analysis of Denotative and Connotative Meanings in Adele’s Song Lyrics "My Little Love": A Semantic Analysis - Wulan Dari; Fadhlur Rahman; M Nazar (Journal of linguistics, culture and communication, 2026)
This paper examines the semantic dimensions in Adele's song “My Little Love” through an analysis of the denotative and connotative meanings contained in the lyrics. The research aims to identify the types of meaning present and explore how these meanings represent emotional interpretations in musical works. The theoretical framework used is James Dickins' theory of connotative meaning to dissect the layers of meaning behind the lyrics. The results show that the song lyrics contain two main categories of meaning. First, the denotative meaning, which presents literal and explicit communication between Adele and her child. Second, connotative meaning, which consists of five subtypes: (1) affective meaning, which expresses deep emotions, (2) attitudinal meaning, which describes the singer's psychological position, (3) basic meaning, which refers to fundamental values, (4) illocutionary meaning that overrides locution, and (5) associative meaning that builds symbolic connections. The findings reveal that denotative meaning serves as the foundation of verbal communication, while connotative meaning presents emotional complexity that includes guilt, vulnerability, maternal love, and loneliness. The interaction between these two types of meaning collectively reflects Adele's personal experience of dealing with divorce and the challenges of being a single mother. This study contributes to the understanding of the use of figurative language in contemporary music and opens up opportunities for further semantic studies of other popular music works to enrich the linguistic discourse in the music industry.